Decentralization Practice in Developing Countries: Lessons for Indonesia - Aditya Wisnu Pradana (Universitas Sultan Ageng Tirtayasa, 2021)
This study seeks to examine the practice of decentralization as a good lesson in Indonesia. This is done by analyzing whether decentralization can be an effective development solution in developing countries through the identification of several reviews of the problems that arise in it. By using a descriptive-qualitative approach, the research presents and describes a phenomenon in its entirety with the author's interpretation. The results of this study found several important things. The case of Indonesia shows that the problem of the minimum quality of apparatus resources in the regions is still a problem in achieving optimal regional autonomy. Strengthening the management of the apparatus in the regions systematically and equally in this case is an effort that must be made to support the practice of decentralization. In addition, providing political education to civil society to encourage the maturity of society in democracy is a strategic step that can be taken to ensure the political commitment of the government in the regions in realizing decentralization practices that lead to the goal of accelerating development based on the principles of justice and the facilitation of democratic values.